Susungan: Tradisi Adat Maanta Mayit Ka Pandan Kuburan - Adam Pramugio Putra; Fira Permata Putri; Iman Ashar Tanjung; M Rifki Haikal; Risky Amalia (Institut Seni Indonesia Padangpanjang, 2025)
Nagari Bukik Tandang, located in Bukik Sundi District, Solok Regency, West Sumatra, has a rich history and traditions deeply rooted in Minangkabau customs. Established by early settlers around 1680, the community of Nagari Bukik Tandang formed with five major clans inhabiting the area. One of the unique traditional customs in this Nagari is